The Role of Islamic Religious Education Teachers in Advancing Generation of the Nation's Children - Asnidar; Mansur; Musta'an Karadjo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Indonesia is a country whose majority population is Muslim. We also encounter many schools with Islamic characteristics such as madrasas. Even in Madrasas, students receive more religious instruction than general schools. In this perspective, the role of Islamic Religious Education Teachers is indispensable in developing students' religious morals which are currently almost forgotten, especially among young people who have been carried away by the times. In the world of formal education, teachers play an important role in educating the nation's children. In addition to teaching, educating, and fostering akhlaqul kharimah, teachers are also role models for their students and become second parents who educate students at school. Moral education is also very important to be taught to students, especially in the present. Where the rapid development of technology, the influence of friends and social media can also make children forget about good manners and have bad morals.